PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DI BIRO ADMINISTRASI UMUM DAN KEUANGAN UNIVERSITAS NEGERI JAKARTA - Waspodo, ag AWS; Ristiani, Rista; Handaru, Agung Wahyu (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
Generally, the purposes of this research are: 1) to describe the leadership style, organizational commitment and organizational citizenship behavior (OCB) 2) to analyze the influence of leadership style towards OCB. 3) to analyze the influence of organizational commitment towards OCB. 4) to analyze the simultaneous influence of leadership style and organizational commitment towards OCB. Population of this research is the employees of the Bureau of Public Administration and Finance, State University of Jakarta. Type of the research is descriptive and the method is explanatory survey. The results of descriptive analysis explain a) selling leadership style is more dominant than the telling leadership style, participative and delegative b) organizational commitment of employees is quite high although normative commitment was still low. c) the OCB of employee was quite good although the dimensions of altruism and civic virtue were not good enough. The results of hypothesis testing explain 1) the influence of leadership style towards OCB of employee Bureau of Public administration and Finance UNJ the leadership style increases the OCB of employee will increase 2) the influence organizational commitment to OCB of employee that the organizational commitment can be predicted OCB of employees will increase. Keywords: Leadership style, Organizational Commitment, Organizational Citizenship Behavior